2009
DOI: 10.1590/s0066-782x2009001100019
|View full text |Cite
|
Sign up to set email alerts
|

Alterações metabólicas, terapia antirretroviral e doença cardiovascular em idosos portadores de HIV

Abstract: SummaryOne of the most recent phenomena related to the acquired immunodeficiency syndrome (AIDS) is the emergence of a new vulnerable population: the elderly. One of the factors that account for this increase is the development of combination antiretroviral therapy (ART), which has provided better quality of life and life expectancy for HIV-positive patients. However, ART is associated with adverse effects such as dyslipidemia, diabetes mellitus and insulin resistance, which are risk factors for cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 71 publications
2
11
0
16
Order By: Relevance
“…Idosos em geral são mais propensos a comorbidades que necessitam de tratamento contínuo com vários medicamentos e, por causa da aids, o uso de antirretrovirais poderá acarretar interações medicamentosas em seu organismo, como também dificuldade em utilizar todos esses medicamentos nos horários corretos. 8,24 Em relação às doenças oportunistas ou intercorrên-cias apresentadas, destacaram-se a candidíase, seguida pela diarreia, anemia, pneumonia e tuberculose. Essas doenças e intercorrências são facilmente confundidas com sintomas associados a várias afecções comuns nessa faixa etária.…”
Section: Discussionunclassified
“…Idosos em geral são mais propensos a comorbidades que necessitam de tratamento contínuo com vários medicamentos e, por causa da aids, o uso de antirretrovirais poderá acarretar interações medicamentosas em seu organismo, como também dificuldade em utilizar todos esses medicamentos nos horários corretos. 8,24 Em relação às doenças oportunistas ou intercorrên-cias apresentadas, destacaram-se a candidíase, seguida pela diarreia, anemia, pneumonia e tuberculose. Essas doenças e intercorrências são facilmente confundidas com sintomas associados a várias afecções comuns nessa faixa etária.…”
Section: Discussionunclassified
“…Another metabolic alteration has been reported in HIV lipodystrophy syndrome (SLD), known as fat redistribution syndrome, which causes an accumulation of fat in the dorso-cervical (buffalo hump) and abdominal region. Fat redistribution with abdominal lipohypertrophy predisposes the patient to cardiovascular disease risk due to visceral fat, directly associated with a higher incidence of changes in serum lipids and insulin resistance, with a rise in risks for the development of Type 2 diabetes [16]. This study is well established as shown in Table 2, classification of cardiovascular risk in these patients have a higher prevalence of medium and high risk.…”
Section: Discussionmentioning
confidence: 75%
“…This fat redistribution with abdominal lipohypertrophy predisposes to risk of cardiovascular diseases, due to the visceral fat direct association with higher incidence of serum lipid alterations as well as insulin resistance, increasing hence the risk of development of type 2 diabetes 18 . Kramer 19 reported dyslipidemia in the HIV patient who makes use of HAART characterized by increased VLDL (the greatest triglyceride transporter) and LDL-cholesterol levels and reduction of the HDL-cholesterol level. The authors also suggest that the facts which would lead the HIV patient to present dyslipidemias are not totally elucidated yet.…”
Section: Discussionmentioning
confidence: 99%